Time Orientation and Mental Accounting: Examining Serial Mediation Effects of Financial Literacy and Impulsivity - Maneesha Singh; Tanuj Nandan (Journal of Financial Therapy, 2024)
With a wide variety of complex financial assets and securities available in the market, individuals often struggle with their financial planning due to a lack of financial literacy, high impulsivity, and short-term time orientation, hampering their financial satisfaction. The current study examines the yet unexplored indirect effect of investors' time orientations on mental accounting through financial literacy and impulsivity. We conducted a cross-sectional survey and collected 162 active investors’ responses via structured questionnaires distributed in both online and offline portals across India to gauge their financial literacy, time orientation, impulsivity, and mental accounting. We used Smart PLS-4 software along with structural equation modeling to test the direct and indirect effects of time orientation on mental accounting. Findings support the statistical significance of the indirect effect of time orientation on mental accounting through financial literacy and impulsivity. In other words, the way an individual perceives time has an impact on the categorization of incomes and expenses. Moreover, impulsiveness and financial literacy play a key role in between. The findings of this study contribute to the discipline by advancing a model for predicting investors’ mental accounting, as well as partially answering the question of why, if mental accounting is so important, many individuals do not use it for their investment decisions. This study’s findings offer suggestions on how investors can be influenced to use this model. Moreover, this study suggests how financial therapy and counseling can play a critical role in improving the financial health and well-being of individuals.
Keywords: Impulsivity; Time-orientation; Financial Literacy; Mental accounting; Investor well-being